2022
DOI: 10.1186/s13041-022-00905-y
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetics: implications for Alzheimer’s disease research and therapy

Abstract: Alzheimer’s disease (AD), a critical neurodegenerative condition, has a wide range of effects on brain activity. Synaptic plasticity and neuronal circuits are the most vulnerable in Alzheimer’s disease, but the exact mechanism is unknown. Incorporating optogenetics into the study of AD has resulted in a significant leap in this field during the last decades, kicking off a revolution in our knowledge of the networks that underpin cognitive functions. In Alzheimer's disease, optogenetics can help to reduce and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 201 publications
(185 reference statements)
0
18
0
Order By: Relevance
“…Other therapeutic approaches that are being pursued include modulation and enhancement of oscillations ( Chan et al, 2021a ; Mirzayi et al, 2022 ). Deep brain stimulation, transcranial magnetic stimulation, and transcranial electrical stimulation are all being explored as ways of modulating activity in AD with some modest improvements seen with these methods ( Laxton et al, 2010 ; Yu et al, 2021 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Other therapeutic approaches that are being pursued include modulation and enhancement of oscillations ( Chan et al, 2021a ; Mirzayi et al, 2022 ). Deep brain stimulation, transcranial magnetic stimulation, and transcranial electrical stimulation are all being explored as ways of modulating activity in AD with some modest improvements seen with these methods ( Laxton et al, 2010 ; Yu et al, 2021 ).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Optogenetics rapidly has become a standard tool in neuroscience research as it permits cell-type-specific targeting and temporally precise activity modulation [ 20 ]; both features are desirable for a gain or loss of function experiments. In the past decade, the optogenetic approach has been increasingly applied in biomedical research and cognitive neuroscience [ 48 , 49 , 50 , 51 ]. The most commonly used methods to deliver functional opsin genes are viruses, in vivo electroporation, and the generation of transgenic animals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that CFC may play a role in Parkinson’s disease as excessive PAC between beta and gamma bands has been observed in advanced-stage patients with movement deficits [ 64 , 88 ]. Abnormal theta–gamma CFC has been implicated in Alzheimer’s disease, as coupled band synchronization plays a critical role in memory functions [ 89 , 90 ]. Also, theta–phase gamma–amplitude coupling has been seen as a marker of Attention Deficit Hyperactivity disorder (ADHD) in children [ 91 ].…”
Section: Neural Oscillations In Cognition and Neurological Disordersmentioning
confidence: 99%